Elinor wonders why. A wonderful journey [videorecording (DVD)] (PBS Distribution, 2022)
Join Elinor, Ari, and Olive as they head out to Hidden Lake for a camping adventure. While exploring the area, they discover that frogs appear to be missing from the lake. Can Elinor and her friends solve the mystery?